Causal Exclusion and Ontic Vagueness. Issue 1 (2nd January 2022) - Silver, Kenneth
ABSTRACT: The Causal Exclusion Problem is raised in many domains, including the metaphysics of macroscopic objects. If there is a complete explanation of macroscopic effects in terms of the microscopic entities that compose macroscopic objects, then the causal efficacy of the macroscopic will be threatened with exclusion. I argue that we can avoid the problem if we accept that macroscopic objects are ontically vague. Then it is indeterminate which collection of microscopic entities compose them, and so information about microscopic entities is insufficient to provide a complete explanation of certain properties of macroscopic objects. After outlining this solution, I consider several objections.